Subcontracting and survival: challenges of small, medium and micro enterprises in Cape Town’s public infrastructure projects - Thobelani Zanaye; Adrino Mazenda; Chamunorwa Huni (SN Business & Economics, 2026)
Abstract Tender subcontracting benefits Small, Medium, and Micro Enterprises (SMMEs) by providing access to markets, financial stability, technical capacity, mentorship, and growth opportunities, while also advancing government objectives of inclusive and sustainable economic development. The paper examined the challenges faced by subcontracted SMMEs involved in public infrastructure projects in the City of Cape Town, South Africa. A qualitative case study design was adopted. The data was collected through comprehensive, in-depth interviews with 10 infrastructure project managers and 36 SMME subcontractors. To ensure diverse representation, maximum variation purposive sampling was employed to select SMMEs with prior experience participating in projects within the infrastructure department. Thematic analysis was used to analyse the data. The findings showed that the sustainability of SMMEs was undermined by weak governance structures and the absence of a formal policy framework regulating subcontracting agreements. Unfair subcontracting practices, financial mismanagement, extortion, and political interference further exacerbated these vulnerabilities. The City of Cape Town and other developing cities should be encouraged to implement clear and enforceable policies that enhance transparency, protect subcontractors, and strengthen skills development. Strengthened subcontracting frameworks can promote stable employment, encourage entrepreneurship, and support more equitable economic development within communities.